System innovation in a post-pandemic world - Proceedings of the IEEE 7th International Conference on Applied System Innovation (ICASI 2021), September 24-25, 2021, Alishan, Taiwan; Lam, Artde Donald Kin-Tak (Boca Raton : CRC Press, 2022)
System Innovation in a Post-Pandemic World contains the papers presented atthe IEEE 7th International Conference on Applied System Innovation (ICASI 2021, Alishan, Taiwan, September 24-25, 2021). The conference received more than 200 submitted papers from 11 different countries, whereby roughly one third of these papers was selected by the committees and invited to present at ICASI 2021. The book provides an integrated communication platform for researchers from a wide range of disciplines including information technology, communication science, applied mathematics, computer science, advanced material science, and engineering. Hopefully, interdisciplinary collaborations between science and engineering technologists in the domains of academia and industry will be enhanced via this unique international network.
Prelims. Advanced Material Science & Engineering. Communication Science & Engineering. Computer Science & Information Technology. Computational Science & Engineering. Electrical & Electronic Engineering. Mechanical & Automation Engineering. Green Technology & Architecture Engineering. Innovation Design & Creative Design. Industrial Design & Design Theory. Cultural & Creative Research. Applied Mathematics. Internet & IOT technology. Others. Index.
Includes bibliographies and index.
Keywords: Balkema Conference Proceedings; Technology